Traumatic Bereavement A phenomenological study (Existential Analysis: Journal of the Society for Existential Analysis, 2012)
This study explores the lived experiences of six traumatically bereaved women. The participants were interviewed and the data was analysed using a Descriptive Phenomenological approach. Five main themes emerged which revealed the phenomenology of Traumatic Bereavement and an existential model for therapeutic work was proposed.
Keywords: Traumatic bereavement; ontological awakening; dasein